A1.6 Vascular adhesion molecule VCAM-1 overexpression in collagen induced arthritis : a model for rheumatoid arthritis vascular dysfunction. (31st January 2014) - Denys, Anne; Clavel, Gaëlle; Semerano, Luca; Lemeiter, Delphine; Boissier, Marie-Christophe
Abstract : Background and Objective: Rheumatoid Arthritis (RA) patients are at risk of developing early coronary heart disease. Cardiovascular risk in RA is attributed to both traditional risk factors and to uncontrolled systemic in ammation over a long period. The aim of this study was to develop a model that would mimic both vascular dysfunction and articular inflammation in RA, using collagen induced arthritis (CIA). We mainly focused on VCAM-1 expression, early marker of vascular activation and dysfunction. Materials and Methods: Arthritis was induced in 11 weeks old C57BL/6 mice with 2 injections (at day 0 and 21) of chicken type II collagen (cCII) emulsioned in complete Freund adjuvant (CFA). Half of mice were fed a fat-enriched diet (Western Diet (WD)) (n = 12) while the other half were fed a standard diet. Control mice (not immunised with cCII) were fed either WD (n = 12) or standard diet (n = 12). The aorta and synovial membrane were removed at day 105 after the first cCII immunisation. We analysed VCAM-1, IL-6 and IL-17 mRNA level in both the aorta and the synovium by real time quantitative PCR (qRT-PCR). VCAM-1 localisation in the aortic sinus layers (intima, media and adventitia) was determined by immunohistochemistry (IHC). Results: Immunised mice fed either WD or standard diet had higher qRT-PCR VCAM-1 expression in aorta vs. non immunised mice (p<0.05). Although all mice groups, constitutively expressed VCAM-1 on aortic sinus endothelial cell monolayer, the whole intimal layer stained for VCAM-1 at IHC in both immunised mice (fed standard or western diet) as well as in non immunised mice fed WD. Conversely, the expression of IL-6 and IL-17 in the aorta was similar in all groups. Conclusion: In CIA, C57BL6 mice display aortic inflammation characterised by VCAM-1 overexpression, independently from the diet (WD or standard diet). C57BL6 CIA might be a pertinent model to study the early mechanisms of large blood vessels vascular dysfunction in RA.